'I Love Jesus Because Jesus Is Muslim': Inter- and Intra-Faith Debates and Political Dynamics in Indonesia. Issue 2 (2nd April 2020) - Hidayati, Mega; van Doorn Harder, Nelly
ABSTRACT: This article discusses the public reactions to a billboard with the message: 'I love Jesus because Jesus is Moslem'. A radical Islamic group placed the billboard in the Indonesian town of Cilacap in 2018 with the goal of discouraging Muslims from attending events celebrating Christmas and New Year. We place the inter-religious debates resulting from the billboard incident within the larger context of Muslim opinions on the figure of Jesus in Islam and Christianity. We furthermore ask how the Indonesian state negotiates Muslim–Christian interreligious dialogues and how its intervention influences the opinions of individual religious and community leaders. Our main conclusion is that, in spite of the fact that deeper engagement between the two communities could yield stronger forms of cooperation or reconciliation when incidents of interreligious strife occur, all involved prefer to avoid it. Instead, they aim to maintain an equilibrium that represents the status quo. Most Muslim and Christian leaders, for various reasons, remain averse to engaging in deeper conversations, especially when it concerns the role of Jesus in their respective religions.